APAKAH MOTIVASI MEMEDIASI PENGARUH PELATIHAN TERHADAP PRESTASI KERJA DAN PENGEMBANGAN KARIR PADA KARYAWAN RSU AISYIYAH KLATEN - Nuur Rohmah Nadzafah; Nur Achmad (LP2M Universitas Bina Bangsa, 2024)
Human resources are a very valuable asset for organizations, and quality human resources are needed for the growth and development of companies. In order to achieve excellence, human resources must have adequate vision and expertise. Qualified employees can be recognized by their knowledge, skills, abilities, and good work ethic. To improve the quality of its employees, companies must provide training and development opportunities. With training, employees can gain new knowledge and values that can be applied to improve their professional performance. This study examines the impact of employee training on job performance and career development, with motivation as a mediating variable. The results of the study showed that employee training had a significant positive effect on work performance and career development. Motivation also plays a significant mediating role in the relationship between employee training and career development. The study concluded that employee training is essential for improving job performance and career development, and that motivation is an important factor in improving the effectiveness of employee training. The findings of this study have implications for human resource management practices, especially in the context of employee training and development